ENHANCING EV CHARGING PERFORMANCE WITH ANNCONTROLLED HYBRID (SOLAR/WIND) SYSTEMS - B Sai Prasanth Naik,; Dr. M. Ramasekhara Reddy,; K. Nagabhushanam, (Utilitas Mathematica, 2025)
This paper explores the enhancement of electric vehicle (EV) charging performance through the integration of an Artificial Neural Network (ANN) controller within a solar/wind hybrid power system. The study focuses on designing a robust, efficient system that makes use of the complementary qualities of wind and sun energy sources to guarantee a steady and dependable supply of power. By incorporating ANN control strategies, the system dynamically adjusts to fluctuations in energy production and demand, optimizing the charging process for EVs. The proposed hybrid system not only improves energy efficiency but also reduces dependency on the conventional grid, promoting sustainable and eco- friendly transportation solutions. Simulation results demonstrate significant performance gains in terms of energy utilization and charging speed, highlighting the potential of ANN-controlled hybrid systems in advancing the EV charging infrastructure.